2015
DOI: 10.1074/jbc.m114.573576
|View full text |Cite
|
Sign up to set email alerts
|

Wilms Tumor Suppressor, WT1, Suppresses Epigenetic Silencing of the β-Catenin Gene

Abstract: Background: Hereditary Wilms tumors are preceded by WT1(Ϫ) clones with an inhibitory chromatin histone pattern established by EZH2. Results: In amniotic mesenchymal stem cells, WT1 suppresses EZH2, derepresses ␤-catenin (CTNNB1), and enhances responsiveness to WNT9b. Conclusion: WT1 regulates transition from the epigenetically silenced chromatin state. Significance: Developmental blockade in nephrogenic rests may be mediated by loss of the WT1-EZH2-CTNNB1 axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
(46 reference statements)
1
25
0
Order By: Relevance
“…In the nucleus of renal progenitors, we previously found that the WT1(ϪKTS) isoform suppresses transcription of a Polycomb histone methyltransferase, EZH2 (6). This event is likely to be essential if the differentiation cascade is to be released by inductive WNT signals from ureteric bud.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the nucleus of renal progenitors, we previously found that the WT1(ϪKTS) isoform suppresses transcription of a Polycomb histone methyltransferase, EZH2 (6). This event is likely to be essential if the differentiation cascade is to be released by inductive WNT signals from ureteric bud.…”
Section: Discussionmentioning
confidence: 99%
“…3B). In previous studies, we noted that the WT1(ϩKTS) isoforms suppress EZH2 protein levels in mesenchymal stem cells (6). If this effect is due to transcriptional inhibition, there should be no effect of WT1(ϩKTS) on the CMV-driven EZH2 expression in fibroblasts.…”
Section: Wt1 Induces An Array Of Mirnas In Mesenchymal Stemmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple signaling pathways have been reported to regulate the balance between self-maintenance and differentiation in NPCs, including FGF, BMP and canonical WNT signals (Barak et al, 2012;Blank et al, 2009;Brown et al, 2011Brown et al, , 2013Carroll et al, 2005;Park et al, 2012), all of which interact with or are activated by WT1 (Akpa et al, 2014;Hartwig et al, 2010;Kim et al, 2010;Motamedi et al, 2014). The FGF ligand FGF20 is transcriptionally activated by WT1 in NPCs (Motamedi et al, 2014) and is connected to NPC proliferation through activation of PI3K-AKT (Barak et al, 2012;Brown et al, 2011), whereas Bmp7 is a WT1 target gene (Hartwig et al, 2010) that promotes NPC proliferation by activation of JNK MAPK (Blank et al, 2009;Motamedi et al, 2014).…”
Section: Gas1 Selectively Modulates the Akt Branch Of The Fgf Signalimentioning
confidence: 99%